Renoprotective effects of calcium antagonists on kidney disease (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 1995)
There has been a growing number of evidence that calcium antagonists provide a salutary effects in preserving kidneys against acute renal ischemia in patients at increasing risk. Their beneficial effects on cellular and mitochondrial calcium may explain the effects on renal hemodynamics and metabolics. It seems, that they do not directly vasodilate kidney vessels but alter the response towards vasoconstrictor agents. This effect may mediate diuretic and natriuretic effect of calcium antagonists. Effects on tubuloglomerular feedback and autoregulation mechanism in the kidneys play an important role in this regards. The above mentioned effects may provide a significant kidney protection and retard the progress of kidney disease.The results of recent studies show that calcium antagonists exert potentially. beneficial effects on several clinical settings including radiocontrast-induced nephrotoxicity and transplant-associated renal insufficiency, particularly cyclosporine A nephrotoxicity and ischemia during harvesting of kidneys.Key words: kidney disease - calcium antagonists renoprotective - hemodynamics - kidney function